The Role of Breastfeeding in Preserving the Health of Mother and Child - Stefanović, Ljiljana (PONS - medicinski časopis, 2024)
Breastfeeding is the cornerstone of infant and young child survival, nutrition and developmentand maternal health. Many studies have shown thant women who breastfeed their children haveovarian or breastcarcinoma, cardiovascular diseases and diabetes type 2 rarely. Also,breastffeding is protective factor for postpartal depression, leads to faster weight loss aftergiving birth, faster return of the uterus, reduces possibility of postpartal hemorrhage. Breastfedchildren are more intelligent, less likely to develop autistic spectrum, less tendency to developobesity and allergies, better immunity. At the time of the pandemic Covid 19, center of gravityof health systems of all countries was put on prevention and combat against new infectivedisease. Family care is neglected. The World Health Organization recommends exclusivebreastfeeding for the first 6 months of life, followed by continued breastfeeding with appropriatecomplementary foods for up to 2 years and beyond. According data of World Healthorganization, in 2015-2021, the percent of infants under six months of age, exclusivelybreastfed reached 48%, ten percentage points higher than a decade earlier and close to the WHOtarget of 50% by 2025. The global target for 2030, however, is to reach 70%. Statistical data onthe proportion of breastfed children and monitoring of breastfeeding rates in the Republic ofSerbia still cannot be obtained from routine health statistics, although they are much needed. Tocompare and monitor breastfeeding rates, as well as for planning activities related tobreastfeeding promotion, data is most often used from MISC, Multiple Indicator Cluster Survey.According to the latest data MISC-a, in the Republic of Serbia 90,4 % children were startedbreastfeeding, but only 12 % of children are exclusively breastfed unil the age of 6 months.
Keywords: breastfeeding; prevention; nutrition; Covid 19